A Qualitative Study of Factors Influencing Unsafe Work Behaviors Among Environmental Service Workers: Perspectives of Workers, and Safety Managers: The Case of Government Hospitals in Addis Ababa, Ethiopia. (June 2022) - Tamene, Aiggan; Habte, Aklilu; Endale, Fitsum; Gizachew, Addisalem
Background: Environmental Service (EVS) is a term that refers to cleaning in healthcare facilities. EVS personnel are exposed to a variety of hazards, including physical, chemical, ergonomic, cognitive, and biological hazards that contribute to the development of diseases and disabilities. Recognizing the conditions that promote unsafe behavior is the first step in reducing such hazards. The purpose of this study was to (a) investigate the attitudes and perceptions of safety among employees and safety managers in Addis Ababa hospitals, and (b) figure out what factors inhibit healthy work behaviors. Methods: The data for this study was gathered using 2 qualitative data gathering methods: key informant interviews and individual in-depth interviews. About 25 personnel from 3 Coronavirus treatment hospitals were interviewed to understand more about the factors that make safe behavior challenging. The interviews were recorded, transcribed, and then translated into English. Open Code 4.02 was used for thematic analysis. Results: Poor safety management and supervision, a hazardous working environment, and employee perceptions, skills, and training levels were all identified as key factors in the preponderance of unsafe work behaviors among environmental service workers. Conclusions: Different types of personal and environmental factors were reported to affect safe work behavior among environmental service personnel. Individual responsibility is vital in reducing or eliminating these risk factors for unsafe behaviors, but management's involvement in providing resources for safe work behavior is critical.